Pre-Carboniferous Tectonic Evolution of the San Rafael Block, Mendoza Province - Cingolani, Carlos Alberto (2017)
The pre-Carboniferous evolution of the San Rafael Block is described in different stages. The first one is referred to the Mesoproterozoic basement derived from a complex plutonic and volcanic protolith of Cerro La Ventana Formation. The signature of this basement indicates a common origin with the present eastern part of Laurentia. The carbonate platform of Cuyania terrane has been drifted away during Early Cambrian to Early Ordovician times. The Ordovician silico-carbonate sequences of the San Rafael Block are unconformably deposited over the basement near the present eastern slope of the Cuyania terrane. Detrital zircon ages show a provenance derived from Mesoproterozoic source. The El Nihuil dolerites with a tholeiitic ocean floor signature considered the southern end of the Famatinian ophiolites were interpreted as a Late Ordovician–Early Silurian extensional event. The collision of Cuyania produced a new west polarity subduction and a magmatic arc, represented by the Devonian Rodeo de la Bordalesa tonalite and the granitoids of the “Agua Escondida Mining District”. The Late Silurian–Early Devonian sequences of La Horqueta and Río Seco de los Castaños formations were deformed during the collision and accretion of the Chilenia terrane against the proto-Andean margin, and recorded an east vergent cleavage developed on the previous deformed rocks. This collision produced the strong angular unconformity between the La Horqueta/Río Seco de los Castaños Formations and the El Imperial Formation (Upper Paleozoic). The new subduction with east polarity characterized the beginning of the Gondwanian cycle. The new magmatic arc was interrupted by the intense Lower Permian deformation of the San Rafael tectonic phase.